Kant vs. Cant: Poe's material sublime. Issue 10 (26th November 2019) - Crebs, Francie
ABSTRACT: Edgar Allan Poe's use of the term 'sublime' is somewhat mysterious, and there is therefore a longstanding tradition of calling on outside theories of this notion to understand it. One of these is that of Immanuel Kant. It is this tradition that will be under scrutiny here. Indeed, virtually all the critics who have used Kant's sublime to understand Poe's have done so on the basis of what the German philosopher called the 'dynamic sublime'. But just as important to his theory is the 'mathematical sublime'. This article will argue that the mathematical sublime needs to be re-injected into analyses of Poe's understanding of this notion, and will propose one avenue for doing so: a comparison of a passage from Kant's paragraphs on the mathematical sublime and Poe's tale 'The Sphinx'. The article will further argue that such a reincorporation of this other sublime into analyses and conceptions of the notion reveals a much more material Poe.